Econometric methods for labour economics - Bazen, Stephen (Oxford : Oxford University Press, 2011)
This is an accessible presentation of the standard statistical techniques used by labour economists. It emphasizes both the input and output of empirical analysis and covers the application of five major econometric methods.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Labor economics -- Statistical methods; Econometrics